Influence of the degree of ergot damage on the productivity elements of winter rye varieties - L. M. Shchekleina; T. K. Sheshegova (Аграрная наука Евро-Северо-Востока)
Under the conditions of the Kirov region in 2020-2022 there were studied 21 varieties of winter rye bred by Russian scientific institutions according to the nature of the relationship in the patho-system "Secale cereale L. – Claviceps purpurea (Fr.) Tul.". Under artificial inoculation of flowers with a suspension of the pathogen all the studied varieties were affected by ergot in the range from 3.17 (Graphite FP) to 34.69 % (Saratovskaya 10), with grain contamination with sclerotia – from 0.13 (Graphite FP, Quail) up to 1.87 % (Amber), which indicates their susceptibility to the disease. However, taking into account the signs of "damage by ergot", "contamination of grain with sclerotia" and "yield" for further breeding for ergot resistance, it is possible to recommend varieties Perepel, Lika and Graphite FP (bred by the Federal Agricultural Research Center of the North-East named N. V. Rudnitsky. The influence of the genotype on the biometry of sclerotia has been revealed. This is indirectly evidenced by the significant variability of their parameters in different varieties of rye, which should be taken into account during the mechanical cleaning of grain. Using the Graphite variety as an example, a significant (P ≥ 095) decrease in the grain content and productivity of an ear has been established when more than two sclerotia are formed in it, and four sclerotia form 1000 grains. With an increase in their number to 11 pieces, this pattern remained unchanged, and the harmfulness of ergot reached 64.05 % (ear grain size), 79.60 % (ear productivity) and 46.32 % (grain size). In the process of regression analysis, it has been established that with an increase in infection of the ear by 1-2 sclerotia, the number of grains in the ear decreases by 4.96 pieces, the mass of grain per ear – by 0.26 g, the grain size – by 2.49 g. The similar calculations with a preliminary analysis of the degree of plant damage can be of prognostic value in assessing the potential harmfulness of ergot.